Emperadores, dioses y heroes de la mitologia romana - Usher, Kerry; Sibbick, John. (Madrid : Ediciones Generales Anaya, 1984)
Discusses life in ancient Rome and presents the myths that civilization has bequeathed us.
Titulo original: Heroes, gods and emperors from Roman mythology.
Includes index.
Keywords: Mythology, Roman; Gods, Roman; Heroes -- Rome; Emperors -- Rome; Mitologia romana; Erromatar mitologia